2013
DOI: 10.1021/nl4015183
|View full text |Cite
|
Sign up to set email alerts
|

Luminous Efficiency of Axial InxGa1–xN/GaN Nanowire Heterostructures: Interplay of Polarization and Surface Potentials

Abstract: Using continuum elasticity theory and an eight-band k·p formalism, we study the electronic properties of GaN nanowires with axial InxGa1-xN insertions. The three-dimensional strain distribution in these insertions and the resulting distribution of the polarization fields are fully taken into account. In addition, we consider the presence of a surface potential originating from Fermi level pinning at the sidewall surfaces of the nanowires. Our simulations reveal an in-plane spatial separation of electrons and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
3
29
1
Order By: Relevance
“…This result is in agreement with calculations by Rigutti et al [51]. (GaN/AlGaN NW heterostructures with AlGaN shell) and Rivera et al [52] (GaN/AlGaN NW heterostructures without shell), and in the same line that the calculations of Marquardt et al [53] for InGaN/GaN NW heterostructures. Therefore, in addition to the polarization-induced vertical separation of electron and holes, the 3D geometry of the nanodisks leads to a radial separation of carriers, which explains the delay of the radiative recombination with respect to the quantum well case.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with calculations by Rigutti et al [51]. (GaN/AlGaN NW heterostructures with AlGaN shell) and Rivera et al [52] (GaN/AlGaN NW heterostructures without shell), and in the same line that the calculations of Marquardt et al [53] for InGaN/GaN NW heterostructures. Therefore, in addition to the polarization-induced vertical separation of electron and holes, the 3D geometry of the nanodisks leads to a radial separation of carriers, which explains the delay of the radiative recombination with respect to the quantum well case.…”
Section: Discussionsupporting
confidence: 93%
“…For example, they modify the radiative decay rate of excitons [8,17] and possibly enhance the coupling between * corfdir@pdi-berlin.de free and bound excitons with profound consequences for the exciton decay dynamics [18,19]. In (In,Ga)N/GaN nanowire heterostructures, the interplay between the polarization and surface potentials may lead to a radial separation of electron and holes, resulting in a dramatic decrease of the internal quantum efficiency in the blue spectral range [20].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently discussed the influence of surface potentials arising from unintentional doping and Fermi level pinning on the electronic properties of axial In x Ga 1−x N/GaN nanowire (NW) heterostructures and identified a nontrivial interplay of surface and polarization potentials [6]. While this study provided a qualitative explanation for the experimentally observed reduction of photoluminescence (PL) intensity for low In contents or thin In x Ga 1−x N layers, we have assumed a homogeneous charge density arising from unintentional ntype doping here.…”
Section: Introductionmentioning
confidence: 99%
“…The recombination energy obtained when assuming a homogeneous doping charge density, as used in Ref. [6], is indicated as a solid red line. Additionally, the case of an ideal, doping-free NW is indicated with a black dashed line.…”
Section: Introductionmentioning
confidence: 99%